Archaeology of the invisible: The scent of Kha and Merit. (May 2022) - La Nasa, Jacopo; Degano, Ilaria; Modugno, Francesca; Guerrini, Camilla; Facchetti, Federica; Turina, Valentina; Carretta, Andrea; Greco, Christian; Ferraris, Enrico; Colombini, Maria Perla; Ribechini, Erika
Abstract: The burial assemblage of Kha and Merit discovered in 1906 and now preserved at the Museo Egizio in Turin (Italy) constitutes the most abundant, complete, and well-preserved non-royal Egyptian burial assemblage ever found. The discoverer of the tomb and director of Museo Egizio, Ernesto Schiaparelli, limited investigations to a few non-unique items, leaving most of the assemblage untouched. His decision has enabled contemporary scholars to study such exceptional archaeological finding with non-invasive approaches that could not be foreseen at the time. Here we show that the volatile compounds emitted by organic materials contained in vessels can be analyzed and detected directly in museums by a transportable mass spectrometer (selected-ion flow-tube mass spectrometry, SIFT-MS). The interpretation of the mass spectrometric data, supported by statistical data analysis, shed new light on the chemical nature of the organic materials preserved in 50 vessels of the Museo Egizio in a completely non-destructive way. Our study proves the reliability of SIFT-MS as a fast-screening method for archaeometric investigations directly in museum, providing the unique possibility to complement, confirm and extend the archaeological research on the use and purpose of archaeological vessels and jars. Highlights: The content of vessels from the burial assemblage of Kha and Merit was investigated. Volatile compounds emitted by organic materials were analyzed by mass spectrometry. A transportable selected-ion flow-tube mass spectrometry (SIFT-MS) was used. SIFT-MS acted as a screening method for archaeometric investigations directly in museum. Information was obtained on most of the amorphous materials contained in the objects.